Postpartum Hemorrhage after Vaginal Delivery Is Associated with a Decrease in Immediate Breastfeeding Success - Roig, Jacqueline; Rekawek, Patricia; Doctor, Tahera; Naert, Mackenzie N.; Cadet, Julie; Monro, Johanna; Stone, Joanne L.; Liu, Lilly Y. (American Journal of Perinatology, 2024)
Objective This study aimed to identify the impact of postpartum hemorrhage (PPH) after vaginal delivery on immediate breastfeeding success.Study Design This is a retrospective cohort study examining the impact of PPH on breastfeeding for nulliparous patients after term, singleton, vaginal deliveries at a large academic institution from 2017 to 2018. Indicators of successful breastfeeding in the immediate postpartum period were measured by the presence of breastfeeding, the need for formula supplementation, the average number of breastfeeding sessions per day, the average amount of time spent at each breastfeeding session, the average number of newborn stools and wet diapers produced daily, and the neonatal percentage in weight loss over the first 2 to 3 days of life.Results A total of 1,904 women met inclusion criteria during the study period, 262 (13.8%) of whom experienced PPH, defined as an estimated blood loss of 500 mL or greater after vaginal delivery. Women who had a PPH had significantly fewer breastfeeding sessions on average (β = −0.06, p-value 0.01) and required more time at each breastfeeding session (β = 0.08, p-value <0.002). Neonates of women with PPH had a larger percentage in weight loss over the first 2 to 3 days of life compared with those without PPH (β = 0.06, p = 0.008).Conclusion Women who experience PPH after vaginal delivery have a decreased number of breastfeeding sessions despite spending more time trying to breastfeed, and an increased percentage in neonatal weight loss over the first 2 to 3 days of life. Further work is needed to elicit the mechanism behind this association; however, it is possible that PPH results in decreased secretion of endogenous oxytocin from the hypothalamic–pituitary axis as a result of hypovolemia. These women may therefore require additional breastfeeding support for successful breastfeeding initiation in the immediate postpartum period.Key Points
Keywords: breastfeeding; postpartum hemorrhage; vaginal delivery